(untitled) (Materiali di Estetica. Terza serie, 2020)
In the Westerbork prison camp Etty Hillesum makes a choice of freedom based on irreducibility of the human being: an irreducibility from every act, fact, human or divine instance - and, even, to every more or less founded value, that is not the human being himself